2007
DOI: 10.1210/en.2006-1440
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Alters the Responsiveness of Smooth Muscle Cells to Insulin-Like Growth Factor-I

Abstract: IGF-I stimulation of smooth muscle cell (SMC) migration and proliferation requires alphaVbeta3 ligand occupancy. We hypothesized that changes in the levels of extracellular matrix proteins induced by alterations in glucose concentrations may regulate the ability of SMCs to respond to IGF-I. IGF-I stimulated migration and proliferation of SMCs that had been maintained in 25 mM glucose containing media, but it had no stimulatory effect when tested using SMCs that had been grown in 5 mM glucose. IGF-I stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 44 publications
6
81
1
2
Order By: Relevance
“…Previously, we showed that IGF-I-stim- ulated IRS-1 phosphorylation and subsequent Grb2 binding were markedly down-regulated in VSMCs that had been maintained in high glucose (e.g. 25 mM) (29). The results from the current study confirm the previous observation that VSMCs in high glucose had a significant reduction in total IRS-1 protein levels at 12, 24, and 48 h compared with cells exposed to normal glucose.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previously, we showed that IGF-I-stim- ulated IRS-1 phosphorylation and subsequent Grb2 binding were markedly down-regulated in VSMCs that had been maintained in high glucose (e.g. 25 mM) (29). The results from the current study confirm the previous observation that VSMCs in high glucose had a significant reduction in total IRS-1 protein levels at 12, 24, and 48 h compared with cells exposed to normal glucose.…”
Section: Discussionsupporting
confidence: 90%
“…In VSMCs, Shc phosphorylation in response to IGF-I depends on SHPS-1 phosphorylation and subsequent SHPS-1 complex assembly (2,29). Although some studies have shown that IRS-1 and Shc are competitive substrates for receptor tyrosine kinase (8,9,64), our results show that competition occurs between SHPS-1 and IRS-1, and this leads to impaired SHPS-1 phosphorylation.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations